2007
DOI: 10.1364/ol.32.003074
|View full text |Cite
|
Sign up to set email alerts
|

All-fiber Mach-Zehnder curvature sensor based on multimode interference combined with a long-period grating

Abstract: A novel Mach-Zehnder interferometer based on a fiber multimode interference structure combined with a long-period fiber grating (LPG) is proposed. The multimode interference is achieved through the use of a MMF section spliced between two single-mode fibers, with a length adjusted to couple a fraction of light into the cladding modes. A LPG placed after the MMF couples light back into the fiber core, completing the Mach-Zehnder interferometer. This novel configuration was demonstrated as a bending sensor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(55 citation statements)
references
References 9 publications
0
55
0
Order By: Relevance
“…By introducing collapsed regions or offset splicing at the splicing points of a PCF and two single-mode fibers (SMFs), one can create a Mach-Zehnder Interferometer (MZI) [6,7]. Both the core mode and cladding mode can be simultaneously induced at one splicing point, propagating along different optical paths.…”
Section: Mach-zehnder Interferometermentioning
confidence: 99%
“…By introducing collapsed regions or offset splicing at the splicing points of a PCF and two single-mode fibers (SMFs), one can create a Mach-Zehnder Interferometer (MZI) [6,7]. Both the core mode and cladding mode can be simultaneously induced at one splicing point, propagating along different optical paths.…”
Section: Mach-zehnder Interferometermentioning
confidence: 99%
“…Fiber optic sensors have got a growing interest due to their well-known superior advantages over conventional sensors, such as compact and integrated structure, immunity to electromagnetic interference, high sensitivity, in situ measurements, and potentially low cost [1,2]. Up to now, the curvature characteristics of fiber sensors have been studied in many works, for example, fiber grating-based sensors using the long period fiber grating (LPFG) [1], fiber Bragg grating (FBG) [2], tilted FBG [3], Mach-Zehnder interferometers (MZIs) based on fiber lateral-offset splicing [4], and two identical fused fiber tapers [5] or multimode fiber combined with an LPFG [6]. Usually, the fabricating process of the grating-based curvature sensors is relatively complicated and high power laser is usually needed [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the curvature characteristics of fiber sensors have been studied in many works, for example, fiber grating-based sensors using the long period fiber grating (LPFG) [1], fiber Bragg grating (FBG) [2], tilted FBG [3], Mach-Zehnder interferometers (MZIs) based on fiber lateral-offset splicing [4], and two identical fused fiber tapers [5] or multimode fiber combined with an LPFG [6]. Usually, the fabricating process of the grating-based curvature sensors is relatively complicated and high power laser is usually needed [2,6]. In this regard, the MZI-based curvature sensors as alternatives have attracted lots of attentions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, all-fiber Mach-Zehnder interferometer (MZI) sensors based on mode interference have increasingly aroused research interest in the past several years, because they are compact and easy to fabricate. For example, Wang and Farrell proposed an all-fiber multimode-interference-based refractometer for chemical sensors [14], Mehta et al investigated multimode-interference-based MZIs for displacement sensors [15], and Frazão et al demonstrated a curvature sensor based on multimode interference combined with a long-period grating [16]. Temperature and strain sensors based on all-fiber MZIs were also widely studied, but employing different multimode fibers (MMFs) [17][18][19][20].…”
mentioning
confidence: 99%